Solubility, swelling, viscosity and gelation properties of flours from ubi (Dioscorea alata Linn.) - Rabanes, Louane Mei; Galvez, Flor Crisanta F. (1995.)
Flours were prepared from purple- and white-fleshed ubi (Dioscorea alata Linn.). Swelling power, solubility, viscosity, minimum concentration required for gelation, and gel strength of the flours were investigated. Results indicated that significant differences existed in the swelling power, viscosity, and gelation properties of the flours. The flour from the white variety exhibited a greater capacity to swell and was more viscous at temperatures above 75°C. Less amount of the flour from the purple-fleshed variety was required to form a gel. That gel exhibited greater strength than the gel from the white ubi flour.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Yam flour